EFFECTS OF MAGHNITE NANOCLAY MODIFICATION AND COMPATIBILIZATION ON THE PHYSICAL AND MORPHOLOGICAL PROPERTIES OF POLY(VINYL CHLORIDE)/POLY(ETHYLENE-CO-VINYL ACETATE) BLENDS - Bouaziz, I; Doufnoune, R; Haddaoui, N; Benachour, D; Baltä-Calleja, F. J (university of el oued/جامعة الوادي, 2019)
In this research work poly(vinyl chloride)(PVC), ethylene vinyl acetate copolymer (EVA), and Maghnite nanoclay (MGT) were used to prepare PVC/EVA nanocomposites. The MGT clay was intercalated with octadecyltrimethylammonium chloride (ODTMA) and grafted with γ-aminopropyltriethoxysilane (APTES). The blend nanocomposites were prepared through the melt mixing of PVC/EVA blend at a weight ratio of 50/50 (wt%/wt%) with 20 wt% of compatibilizer; ethylene vinyl acetate grafted with an alcohol (EVA-g-OH) and 3 wt% of modified MGT clay using a Brabender plastograph. The nanocomposites so prepared were characterized using X-ray diffraction, TGA/DTA, mechanical tests and SEM. The results showed that when PVC was blended with EVA, with the modified MGT and with the compatibilizer, synergistic effects in the thermal stability and mechanical properties were observed.
Article
Keywords: Nanocomposites; PVC; EVA; Maghnite nanoclay; Modification; Compatibilizer.